Insulin Resistance in Nonalcoholic Fatty Liver Disease: Experience from Bangladesh (Bangladesh Critical Care Journal, 2016)
Background: Insulin resistance (IR) has largely been hypothesized as central in multifactorial pathogenesis of nonalcoholic fatty liver disease (NAFLD). This study was aimed to explore the association of IR with NAFLD and nonalcoholic steatohepatitis (NASH).Methods: We enrolled 219 patients of NAFLD with sonographic evidence of fatty changes in liver excluding patients with alcohol intake and other causes of fatty change during June 2012 to July 2014.Liver biopsy was done for 110 patients with elevated ALT of >30 U/L for male and >18 U/L for female. We have measured IR by homeostatic model assessment of insulin resistance (HOMA-IR).Results: Age of the study population was 40.6 ± 10.0 years, male and female was 83 (37.9%) and 136 (62.1%), ALT was 42.0 (16-861) U/L, AST was 32 (16-608) U/L and GGT was 39 (10-243) U/L. According to Asian criteria 54 (25.9%) were non-obese, 139 (64.1%) had metabolic syndrome, 163 (74.8%) were hypertriglyceridemic, 200 (91.3%) had low HDL and 170 (77.4%) had high waist. Hypertensive and diabetic were 58 (26.7%) and 57 (26.1%) respectively. IR was 1.9±1.3 with the range of 0.4 to 9.3 and only 87 (39.7%) were above normal. Of the 110 biopsied, 65 (59.1%) had NASH. Normal and raised IR was associated with 32 (50.8%) and 33 (70.2%) NASH respectively (p < 0.05). Correlation between IR and steatosis, ballooning and fibrosis was not significant except lobular inflammation. IR was similar in NASH (2.2 ±1.6) and non NASH (1.9±1.6).Conclusion: Large proportion of NAFLD patients had normal IR. IR had inconsistent association with histological activity.Bangladesh Crit Care J September 2016; 4 (2): 86-91